How store managers can empower their teams to engage in constructive deviance: Theory development through a multiple case study. (January 2020) - Mertens, Willem; Recker, Jan
Abstract: In this paper, we explore how leaders enable constructive deviance in teams they manage. We report on a qualitative field study of two hierarchical layers of store management in 17 supermarket store teams. We focus on the emergence of constructive deviance – better ways of creating value by departing from common ways of working – and how store leaders can enable this behavior. Our inductive analysis from the multiple case data suggests that store management can enable constructive deviance by combining empowering leadership behaviors with adequate levels of contingent reward and monitoring behaviors. These findings allow us to develop new hypotheses about the linkages between constructive deviance, psychological empowerment, and leadership. We detail implications for store management and we describe several future research opportunities on the concept of constructive deviance, its enablement through empowering leadership, and the relationship between organizational norms and constructive deviance.